2016
DOI: 10.1016/j.rboe.2015.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of platelet-rich plasma on lateral epicondylitis of the elbow: prospective randomized controlled trial

Abstract: ObjectiveTo evaluate the effects of platelet-rich plasma (PRP) infiltration in patients with lateral epicondylitis of the elbow, through analysis of the Disabilities of the Arm, Shoulder and Hand (DASH) and Patient-Rated Tennis Elbow Evaluation (PRTEE) questionnaires.MethodsSixty patients with lateral epicondylitis of the elbow were prospectively randomized and evaluated after receiving infiltration of three milliliters of PRP, or 0.5% neocaine, or dexamethasone. For the scoring process, the patients were aske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 18 publications
1
40
0
5
Order By: Relevance
“…At this stage, 87 studies that did not meet the inclusion criteria were excluded. Twenty eligible RCTs were included in our network meta‐analysis (Figure ). In 13 PRP trials, the PRP preparation contained a high concentration of leukocytes in three trials and was relatively pure with deleted leukocytes in 10 trials .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At this stage, 87 studies that did not meet the inclusion criteria were excluded. Twenty eligible RCTs were included in our network meta‐analysis (Figure ). In 13 PRP trials, the PRP preparation contained a high concentration of leukocytes in three trials and was relatively pure with deleted leukocytes in 10 trials .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty eligible RCTs were included in our network meta‐analysis (Figure ). In 13 PRP trials, the PRP preparation contained a high concentration of leukocytes in three trials and was relatively pure with deleted leukocytes in 10 trials . Most studies measured outcomes at more than 2 months; only five studies measured outcomes at 3 weeks to 2 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] The most common reasons for exclusion were review paper (53), non-tendinopathy (14), injection of active control (7; eg, whole blood, PRP) and non-randomised study (7). Several manuscripts were excluded from this review because they were superseded by papers from the same study with longer follow-up including de Vos et al 29 30 and Peerbooms et al 31 A flow diagram of study identification and selection is shown in figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
“…Çalışma hayatında ise performansı etkileyerek iş gücü kaybına ve maliyet artışına neden olmaktadır (11). LE tedavisine yönelik çok sayıda uygulama mevcut olmakla birlikte tedavinin temel prensipleri ağrının giderilmesi, iyileşme sürecinin hızlandırılması, kola yönelik aşırı yüklenmelerin azaltılması ve hastanın günlük yaşam aktivitelerine geri dönüşünün sağlanmasıdır (6,12 Ruh sağlığı 43,0± 10,5 73,5±11,6…”
Section: Introductionunclassified